The influence of donor body mass index on human pancreatic islet function, structure and islet transplant outcome - Walker, J (2011)
Background: Pancreatic islet transplantation for type-1 diabetes has resulted in considerable success over the past decade. However, the worldwide shortage of pancreatic donors remains a major challenge. In an attempt to expand the donor pool, pancreases from obese organs donors (>30 kg/m²) are now routinely offered to islet transplantation in the UK. In addition, it has been suggested that pancreases from donors with early type-2 diabetes mellitus may also be suitable. However, for both these donor groups, although high islet yields (IEQ) may be obtained, it is unclear whether these islets function optimally. An additional approach to the donor shortage is to minimise the number of donors required per islet recipient. One strategy to achieve this is to use different pharmacological agents to enhance post-transplant islet function. Aims: The aims of this thesis were fourfold; 1) To determine whether islets isolated from high BMI donors function normally in vitro and in vivo; 2) To establish why islet yields are higher from obese donors; 3) To determine whether islets from donors with type-2 diabetes are suitable for islet transplantation; 4) To investigate whether glucagon-like peptide 1 receptor agonist therapy improves post-transplant islet graft function. Results: Stimulated insulin and glucagon secretion, and markers of mitochondrial function (intra-islet ATP content and mitochondrial copy number) were compared in islets isolated from obese (BMI>30kg/m²; n= 27) and non-obese (BMI<28kg/m²; n=25) donors. No differences in secretory function or intra-islet ATP were observed between the two groups. Pancreatic lipid and intra-islet triglyceride concentrations were higher in the obese group. In vivo clinical outcomes of patients transplanted in Oxford and a larger cohort (n=35) in Edmonton, Canada with islets from obese or non-obese donors showed no differences in post-transplant outcomes. Improved islet yields were shown to be a result of improved islet recovery of larger islets, in obese donors. Abnormal insulin and glucagon secretory responses were observed in islets from type-2 diabetic subjects (n=6) and islet amyloid content was significantly higher in diabetes. The glucagon-like peptide 1 receptor agonist, exenatide, administered for 20 weeks, significantly improved graft function in patients whom islet function was impaired. Conclusion: The high lipid environment of islets isolated from donors with high BMI appears not to be deleterious to their function either in vitro or when transplanted, supporting the use of islets from high BMI donors for clinical islet transplantation. However, islet dysfunction and pathological changes indicate that islets from type-2 diabetic donors are unsuitable. Therapeutic options such as exenatide, improve transplanted islet viability and function, and could have a significant role in the future of beta-cell replacement therapy for type-1 diabetes.